The effects of COVID-19 event strength on job burnout among primary medical staff - Xinru Li; Yiwen Song; Bingqin Hu; Yitong Chen; Peiyao Cui; Yifang Liang; Xin He; Guofeng Yang; Jinghua Li (BMC, 2023)
Abstract Background As a global pandemic, The Corona Virus Disease 2019 (COVID-19) has brought significant challenges to the primary health care (PHC) system. Health professionals are constantly affected by the pandemic's harmful impact on their mental health and are at significant risk of job burnout. Therefore, it is essential to gain a comprehensive understanding of how their burnout was affected. The study aimed to examine the relationship between COVID-19 event strength and job burnout among PHC providers and to explore the single mediating effect of job stress and work engagement and the chain mediating effect of these two variables on this relationship. Methods Multilevel stratified convenience sampling method was used to recruit 1148 primary medical staff from 48 PHC institutions in Jilin Province, China. All participants completed questionnaires regarding sociodemographic characteristics, COVID-19 event strength, job stress, work engagement, and job burnout. The chain mediation model was analyzed using SPSS PROCESS 3.5 Macro Model 6. Results COVID-19 event strength not only positively predicted job burnout, but also indirectly influenced job burnout through the mediation of job stress and work engagement, thereby influencing job burnout through the "job stress → work engagement" chain. Conclusions This study extends the application of event systems theory and enriches the literature about how the COVID-19 pandemic impacted PHC medical staff job burnout. The findings derived from our study have critical implications for current and future emergency response and public policy in the long-term COVID-19 disease management period.